Is a reduction in albuminuria associated with renal and cardiovascular protection? A post hoc analysis of the ALTITUDE trial. Issue 2 (13th January 2016) - Heerspink, H. J. L.; Ninomiya, T.; Persson, F.; Brenner, B. M.; Brunel, P.; Chaturvedi, N.; Desai, A. S.; Haffner, S. M.; Mcmurray, J. J. V.; Solomon, S. D.; Pfeffer, M. A.; Parving, H.‐H.; et al.
Abstract : Aims: To investigate whether the degree of albuminuria reduction observed in the ALTITUDE trial is associated with renal and cardiovascular protection, and secondly, whether the reduction in albuminuria was too small to afford clinical benefit. Methods: In a post hoc analysis of the ALTITUDE trial in 8561 patients with type 2 diabetes and chronic kidney disease or cardiovascular disease we examined the effect of albuminuria changes at 6 months on renal and cardiovascular outcomes using Cox proportional hazard regression. Results: The median change in albuminuria in the first 6 months in the aliskiren arm of the trial was −12% (25th to 75th percentile: −48.7_to_ +41.9%) and 0.0% (25th to 75th percentile: −40.2_to_55%) in the placebo arm. Changes in albuminuria in the first 6 months were linearly associated with renal and cardiovascular endpoints: a >30% reduction in albuminuria in the first 6 months was associated with a 62% reduction in renal risk and a 25% reduction in cardiovascular risk compared with an increase in albuminuria. The association between changes at 6 months in albuminuria and renal or cardiovascular endpoints was similar in the two treatment groups (p for interaction >0.1 for both endpoints). Conclusions: The addition of aliskiren to angiotensin‐converting enzyme inhibitor/angiotensin receptor blocker therapy resulted in albuminuria changes that were associated with renal and cardiovascular risk changes. This did not translate into renal or cardiovascular protection because the overall reduction in albuminuria in the aliskiren arm was too small and nearly similar to that in the placebo arm.